The problem of the philosophical foundations and scientific nature of the cosmic ideas of A. L. Chizhevsky - Karako, Petr S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The role of the philosophical principle of determinism as the methodological basis of A. L. Chizhevsky’s cosmic ideas is revealed. The significance of statistical determinism in the development and implementation of his space research program is underlined. Its scientific expression and place in the system of directions of comprehension of socio-natural processes by the science of the 1920–30s are noted. The results of research of modern scientists confirming the basic scientific conclusions of A. L. Chizhevsky are presented. Attention is also drawn to the need for their further comprehension and inclusion in the education system.
Keywords: cosmism; heliotaraxy; statistical determinism; heliobiology; world-historical process; theoretical history; synergetics; mathematical modeling